A subset of virus-specific CD161(+) T cells selectively express the multidrug transporter MDR1 and are resistant to chemotherapy in AML - Alsuliman, Abdullah (Blood, 2017)
The establishment of long-lived pathogen-specific T cells is a fundamental property of the adaptive immune response. However, the mechanisms underlying long-term persistence of antigen-specific CD4(+) T cells are not well-defined. Here we identify a subset of memory CD4(+) T cells capable of effluxing cellular toxins, including rhodamine (Rho), through the multidrug efflux protein MDR1 (also known as P-glycoprotein and ABCB1). Drug-effluxing CD4(+) T cells were characterized as CD161(+)CD95(+)CD45RA(−)CD127(hi)CD28(+)CD25(int) cells with a distinct chemokine profile and a Th1-polarized pro-inflammatory phenotype. CD4(+)CD161(+)Rho-effluxing T cells proliferated vigorously in response to stimulation with anti-CD3/CD28 beads and gave rise to CD161(−) progeny in vitro. These cells were also capable of self-renewal and maintained their phenotypic and functional characteristics when cultured with homeostatic cytokines. Multidrug-effluxing CD4(+)CD161(+) T cells were enriched within the viral-specific Th1 repertoire of healthy donors and patients with acute myeloid leukemia (AML) and survived exposure to daunorubicin chemotherapy in vitro. Multidrug-effluxing CD4(+)CD161(+) T cells also resisted chemotherapy-induced cytotoxicity in vivo and underwent significant expansion in AML patients rendered lymphopenic after chemotherapy, contributing to the repopulation of anti-CMV immunity. Finally, after influenza vaccination, the proportion of influenza-specific CD4(+) T cells coexpressing CD161 was significantly higher after 2 years compared with 4 weeks after immunization, suggesting CD161 is a marker for long-lived antigen-specific memory T cells. These findings suggest that CD4(+)CD161(+) T cells with rapid efflux capacity contribute to the maintenance of viral-specific memory T cells. These data provide novel insights into mechanisms that preserve antiviral immunity in patients undergoing chemotherapy and have implications for the development of novel immunotherapeutic approaches.